KAJIAN KINERJA PEMBANGUNAN KETAHANAN PANGAN PADA BERBAGAI INSTITUSI TERKAIT DI KABUPATEN LAMPUNG BARAT - Busran Hamid; Drajat Martianto; Evy Damayanthi (Food and Nutrition Society of Indonesia, 2008)
The limitation in both human and natural resources lead the Local Government of West Lampung to make a priority in budget allocation. The study was aimed to: 1) identify the policy, programs, and activities related to food security at each government institution,2) evaluate the performance among related institution in food security program and activities implementation, and 3) to develop recommendation for food security program and activities improvement. Secondary data were used to address the mentioned objectives. Role of each institution in food security improvement have been defined including the budget allocation. Content analysis from the regional strategic plan shows that there were programs and activities for each sector directed to improve food and nutrition security. However parts of the written plan haven’t been implemented yet. Performance analysis from those which have been implemented indicates that most of the program and activities were achieving the target. Rice production exceeded the target, infrastructure improved, and food prices stable. Intake of animal food and tubers are lower than nutrition norms of desirable dietary pattern (PPH). The prevalence of under-nutrition was considered low.